Community Care and Concern: Moving Outside School to Build Connections - Callaway-Cole, Larisa; Huerta, Valeria; Ramirez, Blanca; Ramirez, Karina; Seyssel, Ariana; Shaffer, Brooke; Wilcox, Emily (Allies for Education, 2018)
This paper explores ways of reconceptualizing family engagement as occurring outside of the classroom. Through attendance at MICOP (Mixteco Indígena Community Organizing Project) meetings, a Family and Community Engagement course learn new ways of building community. Using student voices from a pre-service teacher education classroom, stories of family, culture, and care are documented.